Effects of water supply on seed development and quality of chickpea cultivars - Ghassemi-Golezani, Kazem; Ghassemi, Saeid (Plant Breeding and Seed Science, 2012)
A split plot experiment (using RCB design) with three replications was conducted in 2012 and seed physiological quality of three chickpea (Cicer arietinum L.) cultivars (Azad, Arman and Jame) was evaluated at seven stages under well and limited irrigation conditions. Maximum seed weight (mass maturity) was achieved at 40-45 days after flowering. However, maximum seed quality was obtained 7 to 10 days after mass maturity, depending on irrigation intervals and cultivars. At earlier harvests, because of immaturity, and at later harvests, due to ageing, seed quality was low. Seed filling rate and maximum seed weight of chickpea decreased with decreasing water supply, but water deficit had no significant effects on seed quality as measured by germination percentage, germination rate and seedling dry weight. Significant differences in seedling dry weight among chickpea cultivars were attributed to significant variation in seed weight affected by genetic constitution.